Impaired erythropoietin synthesis in chronic kidney disease is caused by alterations in extracellular matrix composition. Issue 1 (30th August 2017) - Olmos, Gemma; Muñoz‐Félix, José M.; Mora, Inés; Müller, Anton Gerhard; Ruiz‐Torres, Maria Piedad; López‐Novoa, José M.; Rodríguez‐Puyol, Diego
Abstract: Renal fibrosis and anaemia are two of the most relevant events in chronic kidney disease. Fibrosis is characterized by the accumulation of extracellular matrix proteins in the glomeruli and tubular interstitium. Anaemia is the consequence of a decrease in erythropoietin production in fibrotic kidneys. This work analyses the possibility that the accumulation of abnormal collagens in kidney interstitium could be one of the mechanisms responsible for erythropoietin decreased synthesis. In renal interstitial fibroblast grown on collagen I, erythropoietin mRNA expression and HIF‐2α protein decreased, whereas focal adhesion kinase protein (FAK) phosphorylation and proteasome activity increased, compared to cells grown on collagen IV. Proteasome inhibition or FAK inactivation in cells plated on collagen I restored erythropoietin and HIF‐2α expression. FAK inhibition also decreased the collagen I‐dependent proteasome activation. In a model of tubulointerstitial fibrosis induced by unilateral ureteral obstruction in mice, increased collagen I protein content and an almost complete disappearance of erythropoietin mRNA expression were observed in the ureteral ligated kidney with respect to the contralateral control. Interestingly, erythropoietin synthesis was recovered in obstructed mice treated with proteasome inhibitor. These data suggest that reduced kidney erythropoietin synthesis could be caused by the accumulation of abnormal extracellular matrix proteins.